Preparation and Characterization of Co(II), Ni(II) and Zn(II) Complexes Containing Diazine Ligands - MOBINIKHALEDI, A.; FOROUGHIFAR, N. (Asian Journal of Chemistry, 2010)
Preparation and characterization of some of Co(ll), Ni(ll) and Zn(ll) complexes with diazine ligands including phthalazine, pyridazine and naphthyridines are reported. The complexes [(NH3)4CoL2](ClO4)3 (L = phthala- zine, pyridazine) were prepared by reaction of triflato complex [Co(NH3)5OSO2CF3](CF3SO3)2 with the appropriate ligand in sulfolane. Also some complexes of naphthyridines with Co(ll), Ni(ll), Zn(II) were prepared by reaction of ML2 salt (L = Cl) and the appropriate naphthyridine ligand. However, preparation of [(NH3)4CoL2](ClO4)3 with L = naphthyridines was unsuccessful.